Penggunaan surgical safety checklist (SSC) di kamar operasi: Studi kasus implementasi prinsip etik - Candra, Candra; Arofiati, Fitri (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: A crucial part of being a professional nurse is ensuring patient safety in the operating room. The Surgical Safety Checklist (SSC) is used to prevent errors during surgery and ensure the surgical team performs better. However, in practice, negligence in implementing the SSC still occurs frequently and can lead to ethical violations and patient harm. Purpose: To analyze the application of ethical principles in cases of violations of the Surgical Safety Checklist (SSC) in the operating room. Method: This study used a case report design with a qualitative descriptive approach to describe in-depth real-life experiences in implementing the Surgical Safety Checklist (SSC) in the operating room, specifically related to the application of nursing ethical principles such as autonomy, beneficence, non-harm, and justice. Results: The case of Mrs. D (38 years old) with peritonitis due to bowel perforation demonstrated a failure to implement the SSC (Surgical Safety Checklist) during the handover phase, resulting in the arterial clamp being left in the peritoneal cavity. Analysis showed that this incident violated the principles of non-maleficence and beneficence and demanded moral and professional responsibility from the entire surgical team, especially the nurses as the controllers of patient safety. Conclusion: Adherence to the Surgical Safety Checklist reflects the application of nursing ethics principles and is a key component in ensuring patient safety in the operating room. Keywords: Nursing Ethics; Operating Room; Patient Safety; Surgical Safety Checklist. Pendahuluan: Bagian penting dari menjadi perawat profesional adalah memastikan keselamatan pasien di ruang operasi. Daftar Periksa Keselamatan Bedah (Surgical Safety Checklist/SSC) digunakan untuk mencegah kesalahan selama operasi dan memastikan tim bedah bekerja sama dengan lebih baik. Namun dalam prakteknya, kelalaian dalam menerapkan SSC masih sering terjadi dan dapat menyebabkan pelanggaran etika dan membahayakan pasien. Tujuan: Untuk menganalisis penerapan prinsip-prinsip etika keperawatan dalam kasus kelalaian penggunaan Daftar Periksa Keselamatan Bedah (SSC) di ruang operasi. Metode: Studi ini menggunakan desain laporan kasus dengan pendekatan deskriptif kualitatif untuk menggambarkan secara mendalam pengalaman nyata dalam menerapkan Daftar Periksa Keselamatan Bedah (SSC) di ruang operasi, khususnya terkait dengan penerapan prinsip-prinsip etika keperawatan seperti otonomi, kemurahan hati, tidak membahayakan, dan keadilan. Hasil: Kasus pasien Ny. D (38 tahun) dengan peritonitis akibat perforasi usus menunjukkan kegagalan dalam menerapkan SSC (Surgical Safety Checklist) selama tahap serah terima tugas yang mengakibatkan ketertinggalan klem arteri di rongga peritoneum. Analisis menunjukkan bahwa insiden ini merupakan pelanggaran prinsip non-maleficence dan beneficence serta menuntut tanggung jawab moral dan profesional dari seluruh tim bedah, terutama perawat sebagai pengendali keselamatan pasien. Simpulan: Kepatuhan terhadap Daftar Periksa Keselamatan Bedah mencerminkan penerapan prinsip-prinsip etika keperawatan dan merupakan komponen kunci dalam memastikan keselamatan pasien di ruang operasi. Kata Kunci: Daftar Periksa Keselamatan Bedah; Etika Keperawatan; Keselamatan Pasien; Ruang Operasi.